2022
DOI: 10.1039/d1ta06419c
|View full text |Cite
|
Sign up to set email alerts
|

Layered MAX phase electrocatalyst activity is driven by only a few hot spots

Abstract: The microscopic analysis of the MAX phase microparticles shows that the electrochemical activity of the microparticles is driven by a few particles with an outstanding catalytic activity towards hydrogen evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…7A and B) consisting predominantly of Mo 2 TiAlC 2 , Mo 2 Ti 2 AlC 3 MAX phases, Mo 3 Al 8 , Al 4 C 3 and TiC phases is notably higher than that of the electrode based on the Ti 3 AlC 2 MAX phase. 37 This is consistent with the literature data 12,71 where the Mo 2 TiAlC 2 MAX phase was highlighted as the most active HER catalyst among other MAX phases. According to, 58 the Mo electrode stability decreases under neutral and basic conditions due to the formation of soluble surface species, but the dissolution rate is very low at −0.6 V vs. Ag/AgCl.…”
Section: Resultssupporting
confidence: 91%
“…7A and B) consisting predominantly of Mo 2 TiAlC 2 , Mo 2 Ti 2 AlC 3 MAX phases, Mo 3 Al 8 , Al 4 C 3 and TiC phases is notably higher than that of the electrode based on the Ti 3 AlC 2 MAX phase. 37 This is consistent with the literature data 12,71 where the Mo 2 TiAlC 2 MAX phase was highlighted as the most active HER catalyst among other MAX phases. According to, 58 the Mo electrode stability decreases under neutral and basic conditions due to the formation of soluble surface species, but the dissolution rate is very low at −0.6 V vs. Ag/AgCl.…”
Section: Resultssupporting
confidence: 91%
“…Recent studies have taken one step back, looking into the fundamental electrochemical properties of MAX phases and the possible application of these compounds as (photo)electrocatalysts for energy conversion. 22,31,32 In previous studies, 33,34 MAX showed better catalytic performances when exposed to different light sources. Ta 2 AlC, Cr 2 AlC, Ti 2 AlC and Ti 3 AlC 2 demonstrated improved photoelectrocatalytic H 2 production when illuminated by a 660 nm light source.…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies have taken one step back, looking into the fundamental electrochemical properties of MAX phases and the possible application of these compounds as (photo)electrocatalysts for energy conversion. 22,31,32…”
Section: Introductionmentioning
confidence: 99%
“…58 These are junctions in between Au nanoparticles in which local elds may accumulate, and the molecules are less favoured to diffuse toward the bulk solution. 59,60 Consequently, the MBA molecules, lying on hot-spots, may guarantee a stable SERS signal. It is also reported that self-assembled monolayers (SAMs) of MBA on Au(111) facets foresee a tilted MBA orientation with respect to the Au surface.…”
Section: Papermentioning
confidence: 99%